Carbon‐ion radiotherapy for isolated para‐aortic lymph node recurrence from colorectal cancer. Issue 7 (20th July 2017) - Isozaki, Yuka; Yamada, Shigeru; Kawashiro, Shohei; Yasuda, Shigeo; Okada, Naomi; Ebner, Daniel; Tsuji, Hiroshi; Kamada, Tadashi; Matsubara, Hisahiro
Abstract : Background: The safety and effectiveness of carbon‐ion radiotherapy (CIRT) for isolated para‐aortic lymph node (PALN) metastasis was evaluated retrospectively. Methods: CIRT for isolated PALN metastasis from CRC was performed in 34 cases from June 2006 to August 2015 in our institute. A median dose of 52.8 Gy(RBE) (range, 48‐52.8 Gy(RBE)) was delivered with a median daily dose of 4.4 Gy(RBE) (range, 4.0‐4.4 Gy(RBE)). Results: The median follow‐up duration for all patients was 24.4 months (range, 7‐82.8 months). There were 13 cases (38.2%) who achieved complete response after treatment. The local control rates at 2 and 3 years were 70.1% and 70.1%, respectively. The overall survival rates at 2 and 3 years were 83.3% and 63.0%, respectively. The 3‐year survival rates for Stage I‐III were 68.7%, while those for Stage IV was 0%. The overall survival of cases with rectal cancer or with high CA19‐9 values pre‐CIRT tended to be worse. The median survival period was 41.7 months. Twelve of the 34 patients survived for more than 3 years. There were no adverse effects of Grade 3 or higher. Conclusions: CIRT for isolated PALN recurrence after curative resection for CRC appears effective and safe, and it is considered a promising therapy.